Phenology in a Changing Environment: Assessing and Forecasting the Timing of the Spawning Migration of the Albemarle Sound and Roanoke River Stock of Striped Bass - Nichols, Quentin B (East Carolina University, 2022)
The seasonal timing of key biological events (phenology), such as migrations, can vary greatly and have strong impacts on fisheries and their management. The Striped Bass (Morone saxatilis) population of the Roanoke River undergoes a yearly upstream spawning migration and subsequently becomes susceptible to an estuarine and freshwater fishery that has a seasonal closure set on May 1st each year. This seasonal closure is static each year yet tagging studies of Albemarle Sound/Roanoke River (A/R) Striped Bass stock indicate their migration timing can be highly variable. The objective of this study is to create an ecological forecast of the A/R stock of Striped Bass migration timing. The forecast revealed the overwhelming importance of Roanoke River discharge on A/R stock migration timing, with a consistent indication that late February to early March is when discharge becomes a key factor. This may be of interest to stakeholders involved in the management of the Roanoke River flow regime, especially as impacts of flows on Striped Bass recruitment have been highlighted as an area of future research in the most recent stock assessment. Another implication of this research for management is that the migration timing of Striped Based has shifted earlier in the year in relation to the current seasonal fishery closure. Temperatures in the Roanoke River and overwintering grounds of coastal Virginia have increased over the study period, which could be driving this shift to earlier migration phenology. Nonetheless, despite a high amount of variance explained, the forecast proved to have low predictive skill up until right before the typical spawning timing and was only able to skillfully predict Striped Bass spawning during years with normally timed phenology. Thus, an operational nowcast of Striped Bass spawning phenology would be possible to develop, but additional research would be needed if stakeholders require longer lead times to act on a forecast. A separate analysis using historical egg survey data analyzed the effect of different sampling frequencies on phenology metrics. These metrics were computed based on a hypothetical sampling schedules of between one and five days per week. Accuracy of calculated phenology metrics compared to observed phenology gradually increased with increasing sampling effort. Eggs have not been collected on the Roanoke River since 1993, yet migration phenology has shifted earlier in recent years. Additional efforts to survey Striped Bass eggs on the Roanoke River should be considered to assess if spawning has also shifted earlier and to support development of a potential phenology nowcast, which could be useful for anglers, fisheries managers, and water managers.
Keywords: Sampling Frequency; Striped bass--Spawning--North Carolina--Albemarle Sound; Striped bass--Spawning--Roanoke River (Va. and N.C.); Ecological forecasting--North Carolina--Albemarle Sound; Ecological forecasting--Roanoke River (Va. and N.C.); Phenology